Built heritage perception through representation of its atmosphere - Anetta Kepczynska-Walczak; Bartosz Marek Walczak (Ambiances)
A holistic view on the city was shaped under the influence of such fundamental works as the Image of the city by Kevin Lynch (1960), or Genius loci by Christan Norberg-Schulz (1979). Especially the latter publication defined the identity of places as a resultant of a number of factors, including intangible values, which allowed better understanding of the complexity and richness of the city phenomena Similar assumptions laid foundation for the recommendation on the protection of the historic urban landscape (HUL) adopted during the UNESCO General Conference in 2011. The above-mentioned issues are crucial for visualising built heritage, since not only shapes and dimensions are responsible for the proper understanding of the place. The intangible values are also of great importance. This is the main topic of the paper, which aims at presenting various methods and techniques in reconstructing and representing heritage buildings and areas. This is illustrated by case studies, based on the professional and didactic experience of authors. In particular, traditional hand-drawing techniques and computer-based visualisation methods are compared. Despite the adopted techniques the most important seems not only to achieve a certain level of accuracy but also to reflect genius loci of represented site. Both issues have to be well-balanced to achieve sustainable and satisfactory results.